2014
DOI: 10.4103/0019-509x.146780
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of cervical cancer screening in women visiting a tertiary care hospital of Delhi

Abstract: Background: Cervical cancer being a major cause of morbidity and mortality in women in developing countries, its awareness is essential. Aim: The aim of this study is to assess the knowledge, attitude and practices of women regarding the basic screening test for detection of cancer cervix. Settings and Design: Population based cross-sectional study. Materials and Methods: Cross-sectional prospective study was conducted. Information from consenting participants (450) was collected using structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
17
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 9 publications
(11 reference statements)
8
17
3
2
Order By: Relevance
“…Similarly Das et al observed significantly greater proportions of adequate knowledge among women in higher age group in Delhi. 11 Awareness about STI symptoms: genital lesions and genital discharge among men was observed poor among women. Risky behaviour; multiple sexual partners was observed in few women with non-use of condom.…”
Section: -14mentioning
confidence: 99%
“…Similarly Das et al observed significantly greater proportions of adequate knowledge among women in higher age group in Delhi. 11 Awareness about STI symptoms: genital lesions and genital discharge among men was observed poor among women. Risky behaviour; multiple sexual partners was observed in few women with non-use of condom.…”
Section: -14mentioning
confidence: 99%
“…These findings are similar to observations on a cross-sectional study [19] conducted in hospital settings in the same area. Regarding the knowledge of preventive measures and screening, the performance is dismal as shown in previous studies [18, 20, 21]. Although almost half of the women think that cervical cancer is a preventable disease only 34% of women know about cervical cancer screening and only dismal 11 percent of women have ever undergone test [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The studies consist of different populations such as women and men from different community groups[17202425313235394143454751616669717379808586909293]And attended clinics[2729425259676872757682]Students (nursing/medical/paramedical/nonmedical)[3840464850565860646974818389]Health-care providers (doctors, nurses, and other health workers);[1828365354555657626365667778889194] migrated Indians;[1921262730333437498487] and cervical cancer patients. [23]…”
Section: Methodsmentioning
confidence: 99%